Lift Generation of Compliant Wing Mechanism of Flapping Wing - Yusoff, Hamid; Iswadi Ismail, Noor; Reedzman Mohd Rakmi, Muhammad; Suhaimi, Shafiq; Wisnoe, Wirachman (International Journal of Engineering and Technology, 2018)
Flapping wing micro air vehicles are small, lightweight and can fly in a low Reynolds Number environment. They are capable of flying at low Reynolds number environment with amazing agility by imitating natural flyers like bats and have compliant wings while flapping. The primary goal of this study is to design and fabricate the compliant mechanism of flapping wing for improvement of lift performance of a MAV. The test was carried out in an open-air wind tunnel. Furthermore, the compliant wing mechanism is measured based on Angle of attack, Reynolds number and flapping frequency. The result shows, lower angle of attack produces lower lift coefficient while higher angle of attack (40°) produces higher lift coefficient until it reaches stall where the lift decreases drastically. The compliant wing mechanism at Reynolds number 20000 produces higher lift coefficient compared to higher Reynolds number, 36000. The best flapping frequency for the compliant wing mechanism is 9 Hz which is the highest frequency used in this experiment. The trend of the flapping frequency shows that the lift coefficient increases when flapping frequency increases. The highest lift produced for compliant wing mechanism is at 40° angle of attack, 9 Hz flapping frequency and 20000 Reynolds number.